2017
DOI: 10.5056/jnm16047
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Body Motility for Clinical Assessment in Patients with Refractory Gastroesophageal Reflux Symptoms

Abstract: Background/AimsLittle data exists about esophageal body dysmotility and reflux patterns in refractory gastroesophageal reflux disease (RGERD) patients off therapy. We aimed to evaluate effects of esophageal body dysmotility on reflux parameters in RGERD patients by combining impedance-pH monitoring and high-resolution manometry (HRM). MethodsWe retrospectively reviewed the impedance-pH data and HRM metrics in patients with refractory gastroesophageal reflux symptoms. Impedance-pH monitoring and manometric data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Meanwhile, long-term exposure to acid is negatively correlated with esophageal body motility. 41,42 To the best of our knowledge, few studies have investigated esophageal motility during long-term acid reflux in individuals with CC and GERD. We found that most primary and secondary peristalsis is 26,47 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, long-term exposure to acid is negatively correlated with esophageal body motility. 41,42 To the best of our knowledge, few studies have investigated esophageal motility during long-term acid reflux in individuals with CC and GERD. We found that most primary and secondary peristalsis is 26,47 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Ineffective esophageal motility and large breaks are associated with reflux‐cough events. Meanwhile, long‐term exposure to acid is negatively correlated with esophageal body motility . To the best of our knowledge, few studies have investigated esophageal motility during long‐term acid reflux in individuals with CC and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with reflux esophagitis had a lower DCI than patients without reflux esophagitis in one study (558 mmHg•sec•cm vs 782 mmHg•sec•cm, respectively; P = 0.045). 34 To distinguish the contraction pattern from contractile vigor, the Chicago classification proposed small breaks (< 3 cm) and large breaks (> 5 cm) in the 20-mmHg isobaric contour. The latter is more common in patients with GERD, who have a pathological number of large breaks assessed by HRM, and are characterized by having a significantly prolonged reflux clearance in the supine position and higher esophageal acid exposure time.…”
Section: Ineffective Primary Peristalsismentioning
confidence: 99%
“…It has been reported that there are more reflux episodes, longer acid exposure, and slower esophageal acid clearance in GERD patients with ineffective esophageal motility (IEM) compared with those with normal esophageal motility . Our previous study also demonstrated that refractory GERD patients with IEM had more episodes of weakly acid reflux and long‐term acid reflux than those with normal esophageal motility . To date, it has been impossible to determine whether esophageal dysmotility is the primary cause or a secondary abnormality in the development of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…9 Our previous study also demonstrated that refractory GERD patients with IEM had more episodes of weakly acid reflux and long-term acid reflux than those with normal esophageal motility. 10 To date, it has been impossible to determine whether esophageal dysmotility is the primary cause or a secondary abnormality in the development of GERD.…”
Section: Introductionmentioning
confidence: 99%